(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Nikolayenko Y. The principles of training students of agrarian specialities for professional communication in foreign linguistic environment. The article deals with the analyses of the principles of training students of agrarian specialities for professional communication in foreign linguistic environment. The specific character of each principle in the foreign language training of future agrarian specialists has been determined.